PENGARUH MEDIA PEMBELAJARAN PODCAST TERHADAP KETERAMPILAN BERBICARA BAHASA INDONESIA - Komang Agus Setiawan; I Made Sutama; I Putu Mas Dewantara (Universitas Pendidikan Ganesha, 2022)
This research uses quasi-experimental research. The population in this study This study For this study, a quasi-experimental design was used. The participants in this study are a quasi-experimental research design was adopted for this investigation. Students from SMA Negeri 2 Banjar's Class XI, which was split into Classes XI BABUD 1 and 2, were chosen as the research subjects. Random sampling was used to choose the experimental and control groups. Data on speaking ability were gathered through performance evaluations made during structured observations or observations of specific study samples. The information was then examined using statistical inference. According to the findings, the experimental group's average score fell into the very high category (81.80%), while the control group's score fell into the high category (75.20%). It could be identified that there was a significant difference in speaking skills between the group that uses podcasts as a learning medium and the group that uses Google Meet.